Ffectiveness Of Trunk Exercise In Improving Postural Control Between Right And Left Hemiplegic Patients - Rani, D. Blessy; MPT, A. Rajarajeswari; Pramila, C. Arockia (Journal of Neonatal Surgery, 2025)
Goals A common neurological deficit following a stroke is hemiplegia, often resulting in significant postural control abnormalities. Such impairments increase the risk of falls, leading to substantial economic and social repercussions. The trunk plays a pivotal role in postural control, and deficits in trunk control are frequently observed after brain lesions. This study aims to evaluate the effectiveness of trunk exercises in improving postural control in right and left hemiplegic patients. Methods The study included patients with right and left hemiplegia post-stroke. 15 Participants in each group respectively underwent a structured trunk exercise program aimed at promoting pelvic mobility, trunk rotation, and selective trunk movements. Interventions were assessed for their impact on postural control, balance, and functional outcomes. Outcome measures included the Gross Motor Function Scale (GMFS) and other standardized assessments of trunk control and balance. Discussion The results showed significant improvements in trunk control and balance in both right and left hemiplegic patients following the trunk exercise program. GMFS scores indicated enhanced motor function, and caregivers reported noticeable improvements in upper limb function and overall mobility. These improvements were more pronounced in patients who received targeted trunk exercises. Trunk exercises significantly improve postural control and balance in hemiplegic patients post-stroke. Conclusion The study underscores the importance of incorporating specific trunk exercises in rehabilitation programs for right and left hemiplegic patients. These findings highlight the necessity for tailored interventions to address this population's unique postural control challenges, ultimately enhancing their quality of life and functional independence.